2001
DOI: 10.1007/pl00002422
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-Ray Therapy of Recurrent Pterygium – an Alternative to 90Sr Eye Applicators

Abstract: The combination of pre- and postoperative 20 kV X-ray therapy and microsurgical excision combined with conjunctival autograft is a highly effective treatment to prevent recurrence in the high-risk group of recurrent pterygia and can be recommended as an alternative to postoperative 90Sr beta irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
1
6
0
3
Order By: Relevance
“…This study provides evidence, that the moderately advanced primary and recurrent pterygia are responding remarkably well to radiotherapy -in line with the efficacy of radiotherapy in other benign diseases [20,27,36,37,47,50] -, with neither recurrence nor late complications observed after therapy and during follow-ups in any patient in this study.…”
Section: Introductionsupporting
confidence: 61%
“…This study provides evidence, that the moderately advanced primary and recurrent pterygia are responding remarkably well to radiotherapy -in line with the efficacy of radiotherapy in other benign diseases [20,27,36,37,47,50] -, with neither recurrence nor late complications observed after therapy and during follow-ups in any patient in this study.…”
Section: Introductionsupporting
confidence: 61%
“…Willner and others had presented positive results of 20 kV irradiation on pterygium in people as an alternative to Sr‐90 applicators 9 . According to the dose penetration in depth of water, 15 kV X‐rays seemed to be appropriate for the therapy of CSK and were chosen as an alternative source of irradiation in this series of cases.…”
Section: Introductionmentioning
confidence: 69%
“…However, grave therapyrelevant shortcomings of the industrial quality assurance of ophthalmic plaques as shown by Kaulich et al [10] have to be taken into consideration. Another alternative treatment of more superficial focal tumor manifestations could be the use of soft X-ray irradiation units as shown by Willner et al [31] for the treatment of recurrent pterygia.…”
Section: Discussionmentioning
confidence: 99%